Time series analysis of incomes policies in the United States - J. L. Gutierrez-Camara (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1981)
The old controversy about whether wage and price controls are instrumental or not in bringing down the rate of inflation was never quite buried in the U.S., although after the apparent failure of Nixon's Economic Stabilization Program of 1971-1974 (ESP) to achieve its desired goals, even the enthusiasm of Incomes Policy advocates appeared for a while to have been mitigated. Defeat however, was never acknowledged, by its defenders. All type of ex-post rationalizations were offered as to, why, in the case of controls having been properly implemented and coordinated with more responsible monetary and fiscal policy, they would have eventually succeeded and not been thwarted in holding the reins of an inflation which from a brisk trot before the imposition of the ESP had set forth in an unbridled gallop at the end of it. Vanquishing inflation has certainly never been a pure academic problem since the costs of either living with it or putting an end to it have always been too real for everybody. But the Reagan administration's belief in a supply-side free lunch as an effective weapon against inflation has rekindled the debate. There is an increased willingness to have yet another go at controls of those who always seeing wage inflation as the big culprit do not think that moderate fiscal and monetary restraint together with the measures to reduce costs and boost productivity (as Reagan's administration has set out to do) can alone curb price inflation without the parallel complementary effect of some direct mandatory wage restraint. The purpose here is limited - to take again the skeleton out of the cupboard, namely the U.S. Economic Stabilization Program of 1971-1974 and try to ask some questions similar to the previous quantitative studies about its effects, as well as some other questions which were perhaps not so much looked into before.
Keywords: 330